TYPES OF CODE-SWITCHING FOUND ON NANA MIRDAD'S VIDEO BLOGS - Suadnyani, Linda; I Komang Sulatra (Yavana Bhasha : Journal of English Language Education, 2024)
The phenomenon of code-switching is often found in daily conversations by bilingual and multilingual families. One of the bilingual families in Indonesia is the Nana Mirdad family. In Nana Mirdad’s daily life, she often does code-switching on her video blogs. Therefore, this study aims to determine the types of code-switching found in Nana Mirdad’s video blogs on her YouTube Channel called The White's Family. This study used a descriptive qualitative method to analyze the data, and the theory of Poplack (1980) and Romaine (1995) was used in this study. Based on the result of this study, the researcher found 123 data on the types of code-switching on Nana Mirdad's video blogs. The dominant type of code-switching found on Nana Mirdad’s video blogs on her YouTube Channel is Intra-sentential switching with occurrences of 56%.